PEMBANGUNAN KESADARAN DAYA SAING PARIWISATA INTERNASIONAL PADA KELOMPOK PEMUDA DI BANDAR LAMPUNG.docx - Hasbi Sidik (Nengah Nyappur, 2022)
The purpose of community services is to sharing knowledge, sharping tourism awarness on international tourism industry in Indonesia. As a productive generation and potential entrepreneur in tourism industry, youth people in Bandarlampung were our main audiens. Using Zoom as media platform, this programme intended that the young people could possibly identify tourism sector and involving positively in international tourism development in Bandarlampung province Keywords: Tourism Awareness, International Tourism, Youth, Lampung Province